Phytocannabinoids and schizophrenia: Focus on adolescence as a critical window of enhanced vulnerability and opportunity for treatment - Stark, Tibor; Di Martino, Serena; Drago, Filippo; Wotjak, Carsten T; Micale, Vincenzo (Pharmacological research, 2021)
The recent shift in socio-political debates and growing liberalization of Cannabis use across the globe has raised concern regarding its impact on vulnerable populations such as adolescents. Concurrent with declining perception of Cannabis harms, more adolescents are using it daily in several countries and consuming marijuana strains with high content of psychotropic delta (9)-tetrahydrocannabinol (THC). These dual, related trends seem to facilitate the development of compromised social and cognitive performance at adulthood, which are described in preclinical and human studies. Cannabis exerts its effects via altering signalling within the endocannabinoid system (ECS), which modulates the stress circuitry during the neurodevelopment. In this context early interventions appear to circumvent the emergence of adult neurodevelopmental deficits. Accordingly, Cannabis sativa second-most abundant compound, cannabidiol (CBD), emerges as a potential therapeutic agent to treat neuropsychiatric disorders. We first focus on human and preclinical studies on the long-term effects induced by adolescent THC exposure as a "critical window" of enhanced neurophysiological vulnerability, which could be involved in the pathophysiology of schizophrenia and related primary psychotic disorders. Then, we focus on adolescence as a "window of opportunity" for early pharmacological treatment, as novel risk reduction strategy for neurodevelopmental disorders. Thus, we review current preclinical and clinical evidence regarding the efficacy of CBD in terms of positive, negative and cognitive symptoms treatment, safety profile, and molecular targets.
Keywords: Animals; Neurodevelopment; fytonutrienty; Cannabinoids; Adolescent; lidé; kanabinoidy; Animal model; schizofrenie; toxické psychózy; Adolescence; THC; Schizophrenia; Cannabidiol; Psychoses, Substance-Induced; Phytochemicals; zvířata; mladiství; Humans